2019
DOI: 10.1002/bab.1821
|View full text |Cite
|
Sign up to set email alerts
|

Lutein upregulates the PGC‐1α, NRF1, and TFAM expression by AMPK activation and downregulates ROS to maintain mtDNA integrity and mitochondrial biogenesis in hyperglycemic ARPE‐19 cells and rat retina

Abstract: Hyperglycemia (HG) affects cellular organelle including mitochondrion in retina that diminishes mitochondrial biogenesis by downregulation of nuclear transcription factors peroxisome proliferator‐activated receptor‐γ coactivator‐1 (PGC‐1α) and mitochondrial transcription factor A (TFAM). Mitochondrial dysfunction has been linked to diabetic retinopathy (DR). Carotenoids reported to modulate mitochondrial biogenesis in HG. Aim of the study was to explore the role of lutein, oxidized lutein (purified upon UV oxi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
12
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 28 publications
(12 citation statements)
references
References 38 publications
0
12
0
Order By: Relevance
“…Zhang et al (2018) reported that high glucose caused a time-dependent decrease in the expression of PGC-1a, NRF1 and TFAM in mouse podocytes, and an increase in ROS levels in cells and mitochondria. The study by Nanjaiah and Vallikannan (2019) revealed that hyperglycaemia affected mitochondria in the retina, and diminished mitochondrial biogenesis by downregulation of PGC-1a and TFAM. To further explore the mechanism of action of TRX1, TRX1 overexpression and siRNA methods were used to examine the changes in cell viability, apoptosis, ROS generation and mitochondrial potential.…”
Section: Discussionmentioning
confidence: 99%
“…Zhang et al (2018) reported that high glucose caused a time-dependent decrease in the expression of PGC-1a, NRF1 and TFAM in mouse podocytes, and an increase in ROS levels in cells and mitochondria. The study by Nanjaiah and Vallikannan (2019) revealed that hyperglycaemia affected mitochondria in the retina, and diminished mitochondrial biogenesis by downregulation of PGC-1a and TFAM. To further explore the mechanism of action of TRX1, TRX1 overexpression and siRNA methods were used to examine the changes in cell viability, apoptosis, ROS generation and mitochondrial potential.…”
Section: Discussionmentioning
confidence: 99%
“…There are numerous reports showing that lutein and/or zeaxanthin can modulate expression of several antioxidant enzymes, and can activate the nuclear factor erythroid 2-related factor 2 (Nrf2) signalling responsible for the expression of antioxidant response element (ARE) genes, and, subsequently, the synthesis of antioxidant and detoxification proteins [ 68 , 69 , 76 , 77 , 78 , 79 , 80 , 81 , 82 , 83 , 84 , 85 , 86 , 87 , 88 , 89 ]. It has been reported that DMSO can activate Nrf2 [ 90 ].…”
Section: Resultsmentioning
confidence: 99%
“…Under the action of PGC-1α, the capacity of mitochondrial DNA increased approximately, the mitochondria proliferate, and the density increased, and mitochondrial biosynthesis was activated. PGC-1α can activate the downstream targets NRF1 and NRF2, and then NRF1/2 binds to the nuclear mitochondrial transcription factor TFAM to regulate the replication and transcription of mtDNA [39][40][41], thereby promoting mitochondrial biosynthesis. In myocardial cells, the PGC-1α/NRF1/TFAM pathway is essential for regulating the mitochondrial function and antioxidant response [8].…”
Section: Discussionmentioning
confidence: 99%